Coevolution of institutions and technology in the internet industry: the role of public policy in technological choices - Manhães, Vinícius Toledo (2022)
Recent technological and market shifts in the Internet are raising regulators and policymakers’ concerns towards two different problems: (i) limiting and regulating the constant abuse of market power of CPs, and (ii) ensuring constant improvement of the Internet network infrastructure with the adoption of new technologies such as 5G. These two problems cannot be disentangled as one affect each other, because poly-making affects technology development and vice versa. We approach this challenge through looking at the Internet industry as a complex adaptive system. Our experiments are based on observing simulations using an agentbased model of the industry on the emergent properties of the policy adaptation process. Our simulation builds on Ostrom (2005) Institutional Analysis and Development Framework (IAD). One of the main drivers identified for the adaptation of the system are shown to be evaluative criteria: the policymaker is characterized, in each simulation, by a different profile and varying goals. They are: economic efficiency, innovation, and universal access. Through this model we were able to observe emergent phenomena that act at the “meso-level” of the economy (between the micro- and macro-levels); emerge probabilistically, last for some time, dissipate and create new patterns. In our experiment, we simulated policymakers convicted in their beliefs, that is, the policymaker was more propense to adopt and enforce policies he believes are more efficient. The simulations show the policymaker capacity to influence the system trajectories, even when the result of its actions displays a degree of unpredictability. Whenever the policymaker was successful in achieving the first condition by the issued policies, at least one of these properties was observed: (i) the more competition among ISPs, the more Internet coverage; (ii) the better the Internet infrastructure, the greater competition between CPs and the better the quality of the content provided. However, there were instances when the policymaker actions generated more noise or lead to completely different trajectories to the ones sought by the policymaker. This highlights the importance of the policymaker role, as well as the necessity that his actions are flexible and carefully thought. The results showsthat the same actions generate different results and influence the direction of the path followed by the system. That is, the policymaker shows great capacity to influence the trajectories of the industry, yet the policymaker also shows difficulty in obtaining desired results given the complexity of the system at play.